Measurement of push-rim forces during racing wheelchair propulsion using a novel attachable force sensor system - Miyazaki, Y.; Iida, K.; Nakashima, M.; Maruyama, T.; Yamanobe, K. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2023)
To improve competitive skills, it is important to clarify the relationship between the propulsion motion (the propulsive force in the use of racing wheelchairs optimized for athletes) and aerodynamic drag, which can change during propulsive motion. Therefore, the purpose of this research was to construct a novel force sensor system that is attachable to racing wheelchairs for individual athletes and usable in a wind tunnel facility to examine differences in the push-rim force characteristics of athletes based on the measured results. The system was composed of four two-dimensional component force sensors, batteries, and radio transmitters. From the output of the four two-dimensional component sensors, tangential and radial components of the push-rim force were measured. Three top-class long-distance wheelchair athletes participated in this study, which required each athlete to push a racing wheelchair at 5.56 m/s on a wheelchair roller system in a wind tunnel facility. The force sensor system was mounted on the participants` individual racing wheelchairs. The measured tangential force waveforms were classified as either bimodal or unimodal depending on the athletes` propulsion styles. Although two athletes showed similar propulsion style characteristics, the athlete with more years of experience showed better propulsive work efficiency and repeatability. Therefore, a difference in skill for applying propulsive force during the push phase, which is difficult to estimate by kinematic analysis, could be estimated by using the force sensor system.